Andreas Vesalius 500 years - A Renaissance that revolutionized cardiovascular knowledge - Mesquita, Evandro Tinoco (Rev Bras Cir Cardiovasc, 2015)
The history of medicine and cardiology is marked by some geniuses who dared in thinking, research, teaching and transmitting scientific knowledge, and the Italian Andreas Vesalius one of these brilliant masters. His main scientific work "De Humani Corporis Fabrica" is not only a landmark study of human anatomy but also an artistic work of high aesthetic quality published in 1543. In the year 2014 we celebrated 500 years since the birth of the brilliant professor of Padua University, who with his courage and sense of observation changed the understanding of cardiovascular anatomy and founded a school to date in innovative education and research of anatomy. By identifying "the anatomical errors" present in Galen's book and speech, he challenged the dogmas of the Catholic Church, the academic world and the doctors of his time. However, the accuracy of his findings and his innovative way to disseminate them among his students and colleagues was essential so that his contributions are considered by many the landmark of modern medicine. His death is still surrounded by mysteries having different hypotheses, but a certainty, suffered sanctions of the Catholic Church for the spread of their ideas. The cardiologists, cardiovascular surgeons, interventional cardiologists, electrophysiologists and cardiovascular imaginologists must know the legacy of genius Andreas Vesalius that changed the paradigm of human anatomy.